Investigation of Failure Mechanism of Al2O3 Specimens Subjected to Three-Point Bending Test (Fracture and Structural Integrity, 2019)
Experimental loading and FEM simulation-based approach at macroscale are utilized to investigate the failure mechanisms of Al2O3 ceramics. Experimental characterization of microstructure is carried out using SEM. Recently the microscale models of representative volume of porous alumina ceramics were built on the basis of grain and pore distribution patterns and subjected to uniaxial loading in order to determine effective mechanical characteristics which are utilized for macroscopic simulation in this work. Pre-fracture behavior of specimens undergoes the Drucker-Prager model with non-associated plastic flow rule. Experimental and numerical simulation fracture patterns show that material exhibits mixed mode I+II of crack propagation. Comparison of experimental data and numerical simulation data gives a good agreement.
Keywords: Alumina ceramics; Three-point bending; Crack propagation; Fracture criterion; Experiment; Numerical simulation